Analysis of ESG Disclosure on the Firm Value in Banking Sector IDX 2020-2023 - Hutauruk, Joseph Reynaldo; Rahmiati, Rahmiati; Mentari, Theresia (INVOICE : JURNAL ILMU AKUNTANSI, 2025)
This study examines the impact of Environmental, Social, and Governance (ESG) disclosure on firm value in the banking sector listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. Utilizing a quantitative approach, this research employs secondary data collected through purposive sampling, resulting in a sample of 80 banking companies that met specific ESG disclosure and financial reporting criteria. ESG disclosure data were obtained based on the Global Reporting Initiative (GRI) Standards, specifically GRI 300 (Environmental), GRI 400 (Social), and GRI 2 (General Disclosures), while firm value was measured using the Price-to-Book Value (PBV) ratio. Multiple regression analysis was conducted to assess the relationship between ESG disclosure and firm value. The findings reveal that environmental, social, and governance factors do not have a significant effect on firm value. This suggests that ESG disclosure in the Indonesian banking sector has not yet been a primary determinant of firm valuation, potentially due to factors such as limited investor awareness, weak regulatory enforcement, or prevailing market skepticism regarding the financial relevance of ESG initiatives. These results contribute to the existing discourse on sustainable banking by providing empirical evidence on the limited impact of ESG disclosure on firm value within the Indonesian banking sector. Furthermore, this study underscores the importance of regulatory bodies in promoting ESG disclosure as a key performance indicator for banking institutions. Future research could examine moderating factors such as financial performance, risk management strategies, or the effectiveness of corporate governance frameworks in strengthening the relationship between ESG disclosure and firm value. These insights are valuable for investors, policymakers, and banking institutions in optimizing ESG strategies to maximize firm value and ensure sustainable financial growth.